Mannerism - Shearman, John K. G. (Harmondsworth : Penguin, 1967)
Manierismo was the extreme consciousness of elegant style for its own sake, a passion which unites the cold narcissistic nudes of Bronzino, the elaborate chiselling of Benvenuto Cellini's saltcellar, and the water-games in a duke's garden.
The historical reality -- The arrival of mannerism in visual arts -- Characteristic forms -- A'more cultured age' and its ideals -- Mannerism in the history of art.
Includes bibliographical references (pages 207-208)
Also issued online.
Keywords: Mannerism (Art); Mannerism (Art) -- Europe -- History; Mannerism (Art)